Isolation of bacteriophages against multidrug resistant Acinetobacter baumannii - Hasan Ghajavand; Bahram Nasr Esfahani; Asghar Havaei; Hossein Fazeli; Reyhaneh Jafari; Sharareh Moghim (Wolters Kluwer Medknow Publications, 2017)
Increasing multiple drug resistant (MDR) strains of Acinetobacter baumannii has aggravated curiosity in development of alternative therapy. Bacteriophages are often considered as alternative agents for controlling A. baumannii infections. In the present study two lytic phages for MDR A. baumannii were isolated and their efficacy and host ranges were evaluated. The phages were isolated from hospital wastewater. Electron microscopy revealed that IsfAB78 might belong to Myoviridae and IsfAB39 to Podoviridae. Initial characterization of phages showed that they have narrow host range and failed to infect relative and non- relative bacteria. Both phages decreased the A. baumannii turbidity significantly, indicating that these isolated phages may be considered as candidates for phage therapy.